Virtual Overseer for Examination Using Artificial Intelligence - VARUN R; Pranav P Rao; Manohar S N; Nagsharan A (Indonesian Journal of Information Systems, 2024)
The Virtual Overseer for Examination using AI is a proposed system that utilizes artificial intelligence (AI) to monitor and supervise online exams. The system aims to enhance the credibility and integrity of online exams by detecting and preventing cheating behaviors such as copying answers or using unauthorized materials. The proposed system utilizes computer vision and machine learning algorithms to analyze exam sessions in real time and flag suspicious behaviors for review by human proctors. The system also employs facial recognition technology to authenticate test-takers' identity and ensure that the right person is taking the exam. Overall, the Virtual Overseer for Examination using AI has the potential to revolutionize online education and assessment by providing a secure and reliable platform for conducting remote exams.